The Role of Social Media in Knowledge Sharing Among Remote Teams - Aaron E. Freudenburg (International Journal of Innovative and Applied Finance, 2024)
This study explores how social media platforms facilitate knowledge sharing in remote work environments. Through qualitative interviews and surveys with remote team members across various industries, the research identifies key factors that enhance collaboration and information exchange. The findings suggest that social media not only improves communication but also fosters a sense of community, ultimately leading to increased productivity and innovation.